The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/pola.24848
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of well‐defined pH‐responsive PPEGMEA‐g‐P2VP double hydrophilic graft copolymer via sequential SET‐LRP and ATRP

Abstract: A series of well‐defined double hydrophilic graft copolymers containing poly(poly(ethylene glycol) methyl ether acrylate) (PPEGMEA) backbone and poly(2‐vinylpyridine) (P2VP) side chains were synthesized by successive single electron transfer living radical polymerization (SET‐LRP) and atom transfer radical polymerization (ATRP). The backbone was first prepared by SET‐LRP of poly(ethylene glycol) methyl ether acrylate (PEGMEA) macromonomer using CuBr/tris(2‐(dimethylamino)ethyl)amine as catalytic system. The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 78 publications
(107 reference statements)
1
27
0
Order By: Relevance
“…The progress in preparing transition‐metal‐containing polymers has also benefited from the development of these powerful synthetic methods 33, 47, 48. In particular, for the synthesis of graft copolymer, side chains can be formed in a well‐defined way via ATRP or SET‐LRP initiated by the pendant initiating groups on the backbone via the grafting‐from strategy,49–52 and the living characteristic of ATRP/SET‐LRP enabled it to control both molecular weights and polydispersities of side chains 53–57…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The progress in preparing transition‐metal‐containing polymers has also benefited from the development of these powerful synthetic methods 33, 47, 48. In particular, for the synthesis of graft copolymer, side chains can be formed in a well‐defined way via ATRP or SET‐LRP initiated by the pendant initiating groups on the backbone via the grafting‐from strategy,49–52 and the living characteristic of ATRP/SET‐LRP enabled it to control both molecular weights and polydispersities of side chains 53–57…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the architecture of copolymers played an important role in the properties of micelles, because nonlinear block copolymers exhibited fundamentally different micellization properties compared with linear copolymers 51. In comparison with the corresponding linear counterpart with similar molecular weight, graft copolymers that contain a great quantity of side chains chemically attached onto a linear backbone are endowed with fascinating properties including worm‐like conformation, compact molecular dimension, and remarkable chain end effects that result from their confined and compact structures 51, 57. However, only a few reports were focused on the synthesis and self‐assembly behavior of well‐defined ferrocene‐based graft copolymers 33, 48.…”
Section: Introductionmentioning
confidence: 99%
“…3 Subsequently, SET-LRP was expanded to acrylates, [4][5][6][7][8][9][10][11][12][13][14][15][16][17] methacrylates, 8,[18][19][20][21][22][23][24][25] acrylamides, [26][27][28][29][30][31] methacrylamide, 32 acrylonitrile, 33,34 and monomers containing more complex water soluble side groups, such as sugars, 35,36 N-(2-hydroxypropyl) methacrylamide, 32 dimethylacrylamide, 26 N-isopropylacrylamide, 26,[37][38][39] oligo(ethylene oxide) methyl ether acrylate, 40 oligo(ethylene oxide) methyl ether methacrylate, 41 hydroxyethyl acrylate, 10 hydroxyethyl methacrylate 23 and acryloyl morpholine. 42 At the same time as these developments, the list of solvents used in SET-LRP was expanded to other solvents that in combination with aliphatic N-donor ligands, such as tris[(2-dimethylaminoethyl)...…”
Section: Introductionmentioning
confidence: 99%
“…As is known, atom transfer radical polymerization (ATRP) is suitable to develop this well-defined block copolymer [24][25][26]. Therefore, in this paper, the well-defined diblock copolymer containing PMPS segment is designed for facility the pendent RASi(OCH 3 ) 3 groups to hydrolyze easily into RASi(OH) 3 in a base or acid catalyst, which can subsequently react with TEOS to generate polymeric/silica hybrids [27,28].…”
Section: Introductionmentioning
confidence: 98%